Paciente masculino de 40 años de edad que presenta hipertensión arterial y antecedentes de diabetes mellitus tipo 2 - Cervantes Luna, Dayana Michell (2019)
Hypertension and diabetes are the main causes of morbidity and mortality in the world, currently about 1 billion people are hypertensive whose global prevalence is 25%, according to ENSANUT currently in Ecuador, high blood pressure has multiplied in greater proportion in recent years, so it is among the top ten causes of morbidity and mortality in the country. The study of these pathologies helps improve nutritional management in patients who suffer from it, which is vital to efficiently establish the treatment and thereby prevent complications in the health of people affected, that is why this case has been carried out of study to know the causal factors of these pathologies and to know the factors that collaborate in the reduction of the alterations in the state of health to proceed with a therapeutic diet plan and see the improvements through the follow up.